2015
DOI: 10.1088/1674-1056/24/3/030203
|View full text |Cite
|
Sign up to set email alerts
|

Controllability of fractional-order Chua’s circuit

Abstract: The ultimate proof of our understanding of nature and engineering systems is reflected in our ability to control them. Since fractional calculus is more universal, we bring attention to the controllability of fractional order systems. First, we extend the conventional controllability theorem to the fractional domain. Strictly mathematical analysis and proof are presented. Because Chua’s circuit is a typical representative of nonlinear circuits, we study the controllability of the fractional order Chua’s circui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…1(b). system, [25,26] and filter circuit. [27,28] In this paper, a complexorder derivative is introduced to circuit elements, and many interesting phenomena are found.…”
Section: Introductionmentioning
confidence: 99%
“…1(b). system, [25,26] and filter circuit. [27,28] In this paper, a complexorder derivative is introduced to circuit elements, and many interesting phenomena are found.…”
Section: Introductionmentioning
confidence: 99%
“…Being a counterpart of the integer-order systems, the fractional-order systems are rich in complex dynamics, such as bifurcations, chaos, hyperchaos, etc. [18][19][20][21] The control and synchronization issues of these systems have also been studied. [18][19][20]22] To deal with the associated FDEs, different versions of fractional derivatives, such as Grunwald-Letnikov fractional derivative, Reimann-Liouville fractional derivative, and Caputo fractional derivative, [23] are possible.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] The control and synchronization issues of these systems have also been studied. [18][19][20]22] To deal with the associated FDEs, different versions of fractional derivatives, such as Grunwald-Letnikov fractional derivative, Reimann-Liouville fractional derivative, and Caputo fractional derivative, [23] are possible. Since analytical solutions of nonlinear FDEs are usually not obtainable, the use of the numerical integration method such as the Adams-Basforth-Moulton predictor-corrector scheme (ABM) [24] is common.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Intensive studies confirmed theoretically and physically that the chaotic and hyperchaotic behaviors exist the nonlinear fractional-order systems. [3,[8][9][10][11][12][13][14][15] Meanwhile, synchronization of fractional-order chaotic systems also has attracted increasing attention due to its potential applications in secure communication [16,17] and digital cryptography. [18][19][20] A variety of control schemes have been proposed to control and synchronize fractional-order chaos in infinite or finite time, [21,22] such as active control, [23,24] sliding mode control, [25][26][27] adaptive control, [28] passive control, [29] and impulsive control.…”
Section: Introductionmentioning
confidence: 99%